Beyond economic growth: sustainable development as an alternative approach - Thauan Santos (Revista Conjuntura Austral, 2018)
This paper aims to make a critical review of the concept of economic growth. Hence, a brief presentation of alternative indicators is made. Therefore, some indicators are presented, as well as their limitations, and then the main threats to be faced are highlighted. Recent discussions under the Paris Agreement and Agenda 2030 are considered, which basically aims to cover more variables and issue areas when it comes to sustainable development. Finally, we present some final considerations about the theme, stressing the need to change not only the economic analytical tools of growth and development, but understanding that the concept of sustainable development requires changes in habits, institutions and metrics.